Comprehensive molecular epidemiology of BVDV in yaks (Bos gruniens) in Qinghai, China: high prevalence and dominance of BVDV-1u - Zhi Li; Yuan Han; Yong Fu; Qing Yuan; Shuqin Wang; Xingye Pan; Wanchao Xue; Hong Yin; Shandian Gao; Ru Meng (Frontiers in Cellular and Infection Microbiology)
IntroductionBovine viral diarrhea virus (BVDV) is a major pathogen affecting livestock health in China. However, the current epidemiological status in yaks (Bos grunniens), particularly in Qinghai Province, remains insufficiently understood.MethodsIn the present study, a comprehensive serological and molecular investigation of BVDV in yaks was conducted across broad geographic areas of eight administrative regions including Yushu, Guoluo, Huangnan, Hainan, Haidong, Haixi, Haibei, and Xining in Qinghai Province.ResultsThe results revealed widespread BVDV exposure in Qinghai yak, with an overall antibody prevalence of 84.52% (1158/1370) and substantial herd variation (12.00~98.07%). Active infections were confirmed through antigen detection, revealing prevalence ranging from 0.34% (Haixi) to 4.90% (Huangnan). Genetic characterization identified two circulating subgenotypes: BVDV-1a (n=3) and the predominant BVDV-1u (n=30), with the latter dominating across all regions.DiscussionThese results highlight the endemic circulation of BVDV in Qinghai yak populations and uncover unexpected genetic diversity, emphasizing the need for control measures to mitigate the adverse impacts of BVDV infection in yaks in high-altitude pastoral systems.